Shaping of the Bessarabian society under the Russian rule in 1812–1873 - Skowronek, Anna (Balcanica Posnaniensia. Acta et studia, 2020)
Shaping of the Bessarabian society under the Russian rule in 1812–1873. Bessarabia is a historical region which constituted a part of the Russian Empire in the 19th century. Throughout the whole century of its functioning within the Russian Empire, Bessarabia retained its multiethnic and multicultural identity. Russia began to start to shape the new administration and the social composition of the province making it similar to the rest of the Empire. Most significant changes took place under the rule of Nicholas I in 30-ies and 40-ies of the 19th century, when the governor of Bessarabia and the rest of the so called New Russia was gen. Nicholas Vorontsov. In the result of several legal decrees (Russ. ukaz) some of the groups were joined to the other ones which made it easier to govern the province and gave the Tzars more considerable income from Bessarabia. All the important administrative social reforms in Bessarabia were completed in the early 70-ies when all the laws of autonomy were abolished and Bessarabia’s status was changed from Oblast into Governorate under its own governor In the meantime the province underwent the process of Russification when the central government introduced Russian as the only official language there and Russian law replaced local legal customs. As a result Bessarabia became just like any other traditional Russian region with a meagre chance to revive again.